1987
DOI: 10.1111/j.1365-2125.1987.tb03005.x
|View full text |Cite
|
Sign up to set email alerts
|

The acute haemodynamic effects of intravenous enalaprilic acid (MK422) in patients with left ventricular dysfunction.

Abstract: Intravenous enalaprilic acid (2.5 mg) was given to 11 patients with stable cardiac failure (NYHA functional class II‐IV). Reductions in mean right atrial, pulmonary artery and pulmonary capillary wedge pressure of 25%, 18% and 30% respectively (P less than 0.01), were observed. Cardiac output rose by 13% (NS) and mean blood pressure fell by 20% (P less than 0.01) with a decrease in systemic vascular resistance of 24% (P less than 0.01). Heart rate was unaltered. The haemodynamic effects correlated with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…AI1 of the hemodynamic changes observed in this study are consistent with observations made by others after open-label intravenous administratio,t of ACE inhibitors to patients with congestive heart failure. [15][16][17][18][19][20][21][22][23][24] Effects on enzyme (renin and ACE) activities and hormonal (angiotensin and aldosterone) concentrations after quinaprilat administration are generally consistent with responses observed in previous studies that examined the acute effects of intravenous ACE inhibitors in patients with congestive heart failure 15~17,21-22,23 although none of the other studies examined as extensively the hormonal profiles evaluated here. In this study, predose PRA and plasma concentrations of angiotensin II, aldosterone, norepinephrine, and ANP were in the upper range of or elevated above normal, whereas plasma ACE activity and plasma concentrations of epinephrine and dopamine were within normal ranges.…”
Section: Resultssupporting
confidence: 75%
“…AI1 of the hemodynamic changes observed in this study are consistent with observations made by others after open-label intravenous administratio,t of ACE inhibitors to patients with congestive heart failure. [15][16][17][18][19][20][21][22][23][24] Effects on enzyme (renin and ACE) activities and hormonal (angiotensin and aldosterone) concentrations after quinaprilat administration are generally consistent with responses observed in previous studies that examined the acute effects of intravenous ACE inhibitors in patients with congestive heart failure 15~17,21-22,23 although none of the other studies examined as extensively the hormonal profiles evaluated here. In this study, predose PRA and plasma concentrations of angiotensin II, aldosterone, norepinephrine, and ANP were in the upper range of or elevated above normal, whereas plasma ACE activity and plasma concentrations of epinephrine and dopamine were within normal ranges.…”
Section: Resultssupporting
confidence: 75%
“…We expected CI increase, especially after lowering afterload to the bad left ventricle, accompanied with massive MR [4, 16, 17]. Unchanged CI despite lower left ventricular afterload could be explained by a worsened left ventricular function per se, or possibly by reduced angiotensin II inotropic activation [18], or appearance of silent myocardial ischemia, which could worsen systolic and diastolic heart function.…”
Section: Discussionmentioning
confidence: 99%
“…It has immediate alleviating effects on increased preload and afterload and lacks unfavorable effects upon myocardial oxygenation [3, 4, 5]. Several reports have described the acute hemodynamic effects of ACE inhibitors in chronic heart failure, but in most studies ACE inhibitor was used only with digoxin and diuretics, without other vasoactive treatment [3, 4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanism of action of CEI on the central nervous system is not yet known. Many studies have reported that CEI have depressor effects, with minimal reflex tachycardia, both clinically and in experimental animal models (Pegram & Frohlich 1982;Daly 1985;Hornung & Hillis 1987). Whether administered chronically or acutely, CEI cause less reflex tachycardia than other vasodilating hypotensive agents (Ueno et al 1980).…”
Section: Introductionmentioning
confidence: 99%